Cost Analysis With Use of Expandable Cage or Cement in Single level Thoracic Vertebrectomy in Metastasis. Issue 5 (June 2022) - Katzir, Miki; Rustagi, Tarush; Hatef, Jeffrey; Mendel, Ehud
Study Design: Retrospective case series. Objective: Patient with metastatic cancer frequently require spinal operations for neural decompression and stabilization, most commonly thoracic vertebrectomy with reconstruction. Objective of the study was to assess economic aspects associated with use of cement versus expandable cage in patients with single level thoracic metastatic disease. We also looked at the differences in the clinical, radiological, complications and survival differences to assess non-inferiority of PMMA over cages. Methods: The electronic medical records of patients undergoing single level thoracic vertebrectomy and reconstruction were reviewed. Two groups were made: PMMA and EC. Totals surgical cost, implant costs was analyzed. We also looked at the clinical/ radiological outcome, complication and survival analysis. Results: 96 patients were identified including 70 one-level resections. For 1-level surgeries, Implant costs for use of cement—75 compared to 9000 for cages. Overall surgical cost was significantly less for PMMA compared to use of EC. No difference was seen in clinical outcome or complication was seen. We noticed significantly better kyphosis correction in the PMMA group. Conclusions: Polymethylmethacrylate cement offers significant cost advantage for reconstruction after thoracic vertebrectomy. It also allows for better kyphosis correction and comparable clinical outcomes and non-inferior to cages.